A Comparison of Single Fraction and Multi Fraction Radiosurgery on the Gamma Knife ICON: A Single Institution Review - Joseph P. Loftus, BS; Matthew Shepard, MD; Yun Liang, PhD; Alexander Yu, MD; Stephen M. Karlovits, MD; Rodney E. Wegner, MD (Advances in Radiation Oncology, 2023)
Purpose: Brain metastases are a common development in patients with malignant solid tumors. Stereotactic radiosurgery (SRS) has a long track record of effectively and safely treating these patients, with some limitations to the use of single fraction SRS based on size and volume. In this study, we reviewed outcomes of patients treated using SRS and fractionated SRS (fSRS) to compare predictors and outcomes of those treatments. Methods and Materials: Two hundred patients treated with SRS or fSRS for intact brain metastases were included. We tabulated baseline characteristics and performed a logistic regression to identify predictors of fSRS. Cox regression was used to identify predictors of survival. Kaplan-Meier analysis was used to calculate survival, local failure, and distant failure rates. A receiver operating characteristic curve was generated to determine timepoint from planning to treatment associated with local failure. Results: The only predictor of fSRS was tumor volume >2.061 cm3. There was no difference in local failure, toxicity, or survival by fractionation of biologically effective dose. Predictors of worse survival were age, extracranial disease, history of whole brain radiation therapy, and volume. Receiver operating characteristic analysis identified 10 days as potential factor in local failure. At 1 year, local control was 96.48 and 76.92% for those patients treated before or after that interval, respectively (P = .0005). Conclusions: Fractionated SRS is a safe and effective alternative for patients with larger volume tumors not suitable for single fraction SRS. Care should be taken to treat these patients expeditiously as a delay was shown to affect local control in this study.